Experimental study on the propagation characteristics of the slamming pressures. (1st December 2020) - Duan, Lele; Zhu, Ling; Chen, Mingsheng; Pedersen, Preben Terndrup
Abstract: The ship slamming pressure may exhibit a propagating feature and would have a significant influence on the local response of ship structure. This paper presents an experimental investigation on the characteristics of the slamming pressure, such as the slamming pressure coefficient, time duration, spatial pressure distribution and propagation speed. A series of experiments on the water entry of rigid and elastic wedges have been carried out for deadrise angles ranging from 0° to 45° and for drop heights ranging from 0.1 m to 1.0 m. Wedge plates with varying thicknesses are tested in the experiments to study the effect of structural elasticity on the propagating feature of the slamming pressure. Based on the experimental results, the spatial variation of the slamming pressure is analyzed. Besides, the effects of the water entry velocity, deadrise angle and wedge plate's structural elasticity on the propagating feature of the slamming pressure is studied. For the flat bottom slamming with a deadrise angle of 0°, the slamming pressure instantaneously acts on the structure, which shows no propagating feature and is close to the uniformly distributed pulse load. The propagation of slamming pressure is found to occur when the deadrise angle exceeds 0.2°. When the deadrise angle is between 4° and 45°, the pressure pulse shape is nearly unchanged during the propagation of the slamming pressure, and the ratio between the experimental speed of propagation and Wagner's theoretical speed is about 0.8. The effect of wedge plate flexibility on the slamming pressure is mainly observed in the cases with small deadrise angles. The wedge plate flexibility causes the duration of the slamming pressure to increase and the pressure coefficient to increase or decrease depending on the ratio between pressure duration and the structure's natural period. Highlights: A series of slamming experiments are conducted to determine the propagation characteristics of the slamming pressures. The ratio between the propagation speed of the measured slamming pressure and Wagner's theoretical speed is about 0.8. Systematic wedge drop tests are carried out for the deadrise angles between 0° and 3° with small increments. Four wedge plate thicknesses are considered to study the effect of structural elasticity on the slamming pressure. The effect of elasticity on slamming pressure depends on the ratio of pressure duration to the structure's natural period.